Effects of digital trade export on wage inequality among enterprises: evidence from China - Liping Zhou; Honglin Yuan (Humanities & Social Sciences Communications, 2024)
Abstract The inclusiveness and “fragmentation” of digital trade have created new possibilities for enterprises that used to face disadvantages in traditional trade, which may reshape the income pattern of enterprises. The increase in digital trade exports positively affects the equalization of inter-firm and intra-industry wages, which exacerbates inter-industry wage inequality. Digital trade exports push the median wage upward and reduce the number of low-wage enterprises. However, it is difficult for high-yield export companies to escape the fate of “the top being cut”. Furthermore, digital trade exports improve the margin of export density and inhibit the marginal category of goods and the market margin, thereby promoting wage equalization among enterprises. Furthermore, there are certain heterogeneity effects on various categories of digital trade, varying levels of intensity of Internet use, different types of enterprises, different locations of industrial chains, and the regional pattern in eastern, central, and western areas.